PT Indosat Ooredoo- Hutchison 3 Indonesia (H3I) Financial Performance Segmentation before and After the Merger - Payoka, Netty; Heikal, Jerry (Jurnal Akuntansi Sektor Publik, 2023)
This study aims to analyze the financial performance of PT Indosat Tbk (ISAT) after the merger with PT Hutchison 3 Indonesia (H3I) or Tri Indonesia. PT Indosat Ooredoo Hutchison Tbk (Indosat Ooredoo Hutchison) in 2021 based on net profit margin artio, return on asset ratio and return on equity ratio in 2020 (before the merger) and 2022 (after the merger). This study uses the K-Mean classification analysis approach through SPSS software. The results showed that there were differences in the clusters of PT Indosat Ooredoo Hutchison Tbk (Indosat Ooredoo Hutchison) before the merger and after the merger, namely the 2020 data is in cluster 3, where cluster 3 is a fairly good cluster based on ROA, ROE and NPM performance calculations PT Indosat Ooredoo Hutchison Tbk (Indosat Ooredoo Hutchison). While in the 2022 data PT Indosat Ooredoo Hutchison Tbk (Indosat Ooredoo Hutchison) is in cluster 4, where cluster 4 is cluster B based on calculations of its ROA, ROE and NPM performance. There is an increase in clusters after the merger.Keywords: ROA, ROE, NPMÂ Â